2021
DOI: 10.1097/qco.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus infections in children

Abstract: Purpose of review Staphylococcus aureus is the most common invasive bacterial pathogen infecting children in the U.S. and many parts of the world. This major human pathogen continues to evolve, and recognition of recent trends in epidemiology, therapeutics and future horizons is of high importance. Recent findings Over the past decade, a relative rise of methicillin-susceptible S. aureus (MSSA) has occurred, such that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
10
0
1
Order By: Relevance
“…In a systematic review and meta-analysis, it was reported that the mortality rate from S. aureus bacteremia was 18.1%, 27.0%, and 30.2% at 1 month, 3 months, and 1 year, respectively [ 2 ]. S. aureus is also the leading invasive bacterial pathogen in children in many parts of the world [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review and meta-analysis, it was reported that the mortality rate from S. aureus bacteremia was 18.1%, 27.0%, and 30.2% at 1 month, 3 months, and 1 year, respectively [ 2 ]. S. aureus is also the leading invasive bacterial pathogen in children in many parts of the world [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed high resistance to the majority of protein-degrading enzymes and hence continue to operate in the digestive tract after consumption. Developing an impressive list of protein toxins is crucial to S. aureus pathogenicity (Cassat and Thomsen 2021). These can function alone or in combination to induce various human disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Skin infection with epidermolytic toxin-producing staphylococci is the cause of acute epidermal necrolysis (Ritter’s disease in infants or Lyell’s disease in young children) [ 6 ]. Bacteremia is usually complicated by metastatic abscesses, which are peculiar elements of invasive inflammatory lesions of S. aureus [ 7 ], with different localizations that can reach the skeletal system, causing the destruction of bone tissue and septic arthritis [ 8 ]. In patients with underlying or recent lung disease, this bacterium can lead to the formation of abscesses and lung consolidation.…”
Section: Introductionmentioning
confidence: 99%